Stress and Personal Well-being among a Sample of Iranian Disabled Veteran's Wives. - Alireza Agha Yousefi; Nasim Sharif (Iranian Journal of Psychiatry, 2010)
The aim of this study was to compare overall life satisfaction, subjective well-being, family stress, and stress symptoms of wives of three groups of Iranian disabled veterans.Participants included 97 wives of three groups of disabled veterans (Group 1with 25-49% disability; Group 2 with 50-69% disability; and Group 3 with larger or equal to 70% disability). The participants were selected randomly by computers of Iranian Martyrs and Veterans Foundations. Personal Well-being Index-Adult, Family Inventory of Life Events and Changes and Stress-related Symptoms Inventory were used to measure overall life satisfaction, family resources of stress and stress symptoms. Data were analyzed by ANOVA and linear multivariate regression analysis.Results showed that there are no differences in stress symptoms among the 3 groups. However, the wives of group 2 showed less stress and more global life satisfaction and subjective well-being; whereas, wives of group 3 showed more family stress and less global life satisfaction and subjective well-being. However, the wives of group 1 showed less global life satisfaction, subjective well-being and less family stress.Based on other studies, the results of group 1 is abnormal. This abnormality in results is due to two reasons: first, the participants tried to show poorer quality of life. Second, these women have not received enough facilities and services. Therefore, they lost their natural homeostasis. It seems that the last reason is more real because of equality in stress symptoms between the 3 groups.